Q: 5x plus x - 6x plus 2x equals 9?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

No. 3x plus 2x = 5x. 3x multiplied by 2x = 6x²

2x + 7 + 5x - 4 - x = (2x + 5x - x) + (7 - 4) = 6x + 3

0. 6x + 3 = 5x + 141. 6x = 5x + 11 [subtracting 3]2. x = 11 [subtracting 5x]

It simplifies to: 12 -6x

2x + 9 = 6x + 1 9 - 1 = 6x - 2x 8 = 4x x = 2

Related questions

6x - 2x + 5x - 3First you want to have the x's by theirselves and the numbers by themselvesIt will still be:6x - 2x + 5x - 3Here, you do 6x - 2x.4x + 5x -3Then you combine 4x + 5x.9x - 3Simplified just like that

No. 3x plus 2x = 5x. 3x multiplied by 2x = 6x²

2x + 7 + 5x - 4 - x = (2x + 5x - x) + (7 - 4) = 6x + 3

-6x+3 = -7-5x 7+3 = 6x-5x 10=x

0. 6x + 3 = 5x + 141. 6x = 5x + 11 [subtracting 3]2. x = 11 [subtracting 5x]

It simplifies to: 12 -6x

3x+5x-2x = 24 6x = 24 x = 4

6x - 8 + 2x - 5 = 7 - 2x ?

2x + 9 = 6x + 1 9 - 1 = 6x - 2x 8 = 4x x = 2

6x^2 + 5x + 1 = (3x +1) (2x + 1)

-5x+1 = 6x -5x-6x = -1 -11x = -1 x = 1/11

5x+15 = 6x-10 5x-6x = -10-15 -x = -25 x = 25